Problematika Tindakan Penyanderaan Sebagai Salah Satu Upaya Penagihan Pajak Di Indonesia - Gidion Samuel Manurung; Hafidz Taqullah Rahman; Lisa Fitri Lestari; Ferry Irawan (PT WIM Solusi Prima, 2022)
One of the efforts made by the Directorate General of Taxes to collect tax debts that have not been paid off by the tax insurer is taking hostage (gijzeling). Gijzeling can be defined as a temporary restraint on the freedom of the tax bearer by placing him in a certain place. In the implementation of gijzeling, there are pros and cons regarding whether or not taking hostage is a violation of the human rights of the tax payer. In addition, questions arise regarding the effectiveness of the implementation of gijzeling on tax debt collection and state revenues as well as obstacles in its implementation. This study uses a qualitative method with a literature study approach. The results of this study indicate that the implementation of gijzeling does not violate the human rights of the tax bearer. The implementation of hostage taking in Indonesia is also quite effective, although it faces several obstacles, both from the DGT side, taxpayers, other agencies, and related regulations. Salah satu upaya yang dilakukan Direktorat Jenderal Pajak untuk menagih utang pajak yang tidak kunjung dilunasi oleh penanggung pajak adalah penyanderaan. Penyanderaan didefinisikan sebagai pengekangan sementara waktu kebebasan penanggung pajak dengan menempatkannya di tempat tertentu. Dalam pelaksanaan penyanderaan terjadi pro dan kontra mengenai benar tidaknya bahwa penyanderaan merupakan pelanggaran terhadap Hak Asasi Manusia (HAM) dari penanggung pajak. Selain itu muncul pertanyaan mengenai efektivitas pelaksanaan penyanderaan terhadap penagihan utang pajak dan penerimaan negara serta kendala dalam pelaksanaannya. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan. Hasil dari penelitian ini menunjukkan bahwa pelaksanaan penyanderaan tidak melanggar HAM penanggung pajak. Pelaksanaan penyanderaan di Indonesia juga tergolong efektif walaupun menghadapi beberapa kendala baik dari sisi DJP, wajib pajak, instansi lain, maupun peraturan terkait.